2017
DOI: 10.1016/j.cell.2017.02.007
|View full text |Cite
|
Sign up to set email alerts
|

A Phase Separation Model for Transcriptional Control

Abstract: Summary Super-enhancers are large clusters of enhancers that control transcription of genes with prominent roles in cell-type specific processes in healthy and diseased states. A model that explains the spectrum of observations regarding super-enhancer formation, function and dissolution is lacking. Phase-separated multi-molecular assemblies provide an essential regulatory mechanism to compartmentalize biochemical reactions within cells. We propose that a phase separation model explains features of transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,248
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,453 publications
(1,391 citation statements)
references
References 84 publications
68
1,248
6
1
Order By: Relevance
“…The accuracy achieved by using our energy landscape model in predicting the effects of compartmentalization, as seen by Hi-C and 3D FISH, supports the plausibility of microphase separation being the physical process driving compartmentalization in chromosomes (17,(34)(35)(36) (Fig. 4).…”
Section: Significancementioning
confidence: 69%
“…The accuracy achieved by using our energy landscape model in predicting the effects of compartmentalization, as seen by Hi-C and 3D FISH, supports the plausibility of microphase separation being the physical process driving compartmentalization in chromosomes (17,(34)(35)(36) (Fig. 4).…”
Section: Significancementioning
confidence: 69%
“…These quantities cannot be derived from the empirical conformation capture data and requires complementary method, such as single particle tracking [24,25]. The present analysis reveals also the statistics of complex matter at the transition point between liquid and gel [26,27] and also how transcriptional bursting dynamics is modulated by the random architecture of chromatin sub-organization. To validate the heterogeneous RCL model, we reconstructed multiple TAD reorganization during three successive stages of cell differentiation: mouse embryonic stem cell (ESC), neuronal precursor cells (NPC) and mouse embryonic fibroblasts (MEF).…”
Section: Discussionmentioning
confidence: 85%
“…Although the small size and compact nature of these transcription sites means that their structural details have yet to be observed directly, the possibility that miniature nuclear bodies form at each active gene has recently been considered (Herzel et al 2017). Moreover, theoretical considerations of transcriptional regulation have led to the suggestion that super enhancers reflect the formation of compartments involving transcriptional regulators, nascent transcripts, and other chromatin components (Hnisz et al 2017). …”
Section: Discussionmentioning
confidence: 99%
“…The other deals with the physical and functional organization of the interchromatin space, a prominent feature of which is the presence of a variety of nuclear bodies that are now thought to reflect the formation of liquid-liquid phase-separated compartments (Mao et al 2011; Zhu and Brangwynne 2015). Indeed it has recently been suggested that both of these organizational principals could be in operation at sites of RNA polymerase II (pol II) transcription (Hnisz et al 2017). However, many questions still remain about the formation and dynamics of individual loop structures and the detailed structure and organization of transcription sites in living cells.…”
Section: Introductionmentioning
confidence: 99%